Impact of Climate Change-Induced Flooding Water Related Diseases and Malnutrition in Borno State, Nigeria: A Public Health Crisis - Abdullahi Tunde Aborode; Oche Joseph Otorkpa; Abdulkareem Olakilekun Abdullateef; Ogun Sedoten Oluwaseun; Grace Adeola Adegoye; Nenger Jerome Aondongu; Iyanuoluwa Oyedeji Oyetunji; Adewunmi Akingbola; Godfred Yawson Scott; Barakat Olajumoke Kolawole; Joel J Komakech (Environmental Health Insights)
Climate change-induced flooding has caused public health crises in Borno State, Nigeria, which influence the increase of waterborne diseases and malnutrition. Flooding disrupts water and sanitation systems, creating breeding grounds for waterborne diseases such as cholera, malaria, and diarrheal illnesses. The displacement of communities and destruction of agricultural infrastructure due to flooding further increase food insecurity, leading to malnutrition. This paper examines the interplay between flooding, waterborne diseases, and malnutrition in Borno State, highlighting the urgent need for climate adaptation strategies and strengthened healthcare systems to mitigate these public health challenges. Additionally, it highlights the double burden of conflict and climate change where ongoing conflicts impede efforts to mitigate and adapt to climate change. Finally, this paper outlines the socio-economic impacts of flooding and proposes interventions to mitigate the effects of flooding.